Comparative assessment of ethnobotany and antibacterial activity of Moringa oleifera Lam. in Nepal - Awasthi, Manisha; Pokhrel, Chandra; You, Young-Han; Balami, Sujan; Kunwar, Ripu; Thapa, Santosh; Kim, Eui-Joo; Park, Ji-Won; Park, Jae-Hoon; Lee, Jung-Min; Kim, Yoon-Seo (Ethnobotany Research and Applications, 2023)
Background: Moringa oleifera Lam. (Miracle tree) is traditionally used as food, vegetable and medicine in different parts of Nepal, to be precise in lowland Tarai. This study aimed at documenting the ethnobotanical knowledge regarding the use of M. oleifera, screening and testing the phytochemicals obtained from different parts (root, bark, leaves, and seeds) of the species and comparing the traditional and lab-based information for advancement in bioprospecting. Methods: Assessment of ethnobotanical use of M. oleifera was carried out using questionnaire survey and informal meetings while the laboratory experiments were performed to appraise the chemical constituents and their activities. The crude methanolic extract of different plant parts of M. oleifera was prepared by cold percolation method and then qualitative phytochemical screening was done following standard protocols. The antibacterial activities of different plant parts were tested using agar-well diffusion method against five different human pathogenic bacteria namely Bacillus subtilis, Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa and Staphylococcus aureus. Results: The plant is being used in 16 districts of lowland Tarai of Nepal for the treatment of 22 ailments including six potentially bacterial ailments: inflammation, tuberculosis, hysteria, diabetes, piles and tumors. Of the five useful plant parts, leaf, root, fruit/seed and bark were frequently harvested while the flower was least used. Analogous to the ethnomedicinal uses, phytochemical compounds of the plant, flavonoids, tannins, phenols, and glycosides exhibited the strong antibacterial activities. The extract from bark showed the higher zone of inhibition followed by leaf and seed, revealing their high potentials for pharmacology. Bark showed the high antibacterial activity against B. subtilis followed by leaf, whereas seed shows its best against S. aureus and root against E. coli. Conclusions: M. oleifera is a promising medicinal plant based on our ethnobotanical survey and laboratory assessment. More research on its ethnomedicinal and biochemical capabilities is needed. Documentation and comparative assessment of traditional knowledge and phytochemical findings might lead a consented and conscientious avenue for bio-prospecting and novel drug discovery. Keywords: Miracle tree, crude extracts, agar-well diffusion method, phytochemicals, ethnomedicine, bioprospecting.